Efektifitas Pelayanan Jasa Melalui Program Kalimasada Untuk Meningkatkan Kesadaran Administrasi Kependudukan di Kelurahan Sidosermo - Aenun Nadila, Indah; Aminah, Siti (PADMA, 2024)
Population administration is a form of public service provided by the government to meet the needs of the community. The Population and Civil Registration Office of Surabaya City launched a new innovation to fulfill the population administration needs of Surabaya residents called the Community Environment Area Aware of Population Administration, known as KALIMASADA. This program operates with the assistance of neighborhood representatives (RW) through cadres and Ningminduk as neighborhood unit representatives (RT) with the aim of facilitating the community in managing population administration easily, efficiently, and effectively. It also aims to determine the effectiveness of administrative services in raising population administration awareness among the community. The method used is descriptive qualitative, utilizing several data variables to measure the program's effectiveness. According to the research conducted, it is known that the effectiveness of the Kalimasada program has been successful in increasing population administration awareness among Sidosermo residents, as all variables have been well implemented according to target data and have successfully achieved the overall target data